Numerische Untersuchung des Verformungs- und Bruchverhaltens von einkristallinem Wolfram auf mikroskopischer Ebene - Bohnert, Christoph (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
The aim of the present work is to describe the deformation and fracture behavior of single crystal tungsten at the microscopic scale by using the ?nite element method. Therefore, the studies focus mainly on the in?uence of crystal orientation as well as the investigation of crack initiation and crack propagation. With a defined crack propagation model, the simulations of microbending allows for evaluating the details of the fracture process more accurately and supported the experimental studies.